Evaluation des paramètres biochimiques chez les femmes enceintes atteintes d’hypertension gravidique - BOUABDALLAH, Amina; BOUKHORSA, Noria (My University, 2021)
Pregnancy is a natural state which requires important physiological, anatomical and biological adaptations of the maternal organism. However, this physiological condition can come with serious health risks, and may contribute to the development of complications. Pregnancy hypertension is the most common pathology during pregnancy responsible for severe maternal and fetal morbidity and mortality. This is one of the primary concerns of stakeholders in women's and children's health all over the world. The present study involved 44 women, including 22 hypertensive pregnant women and 22 normo-tensive pregnant women. Maternal complications were more frequent in patients who had a PAS≥160mmHg or a rate of 27%, and a PAD≥ 110 mmHg or 18%. Analysis of biochemical parameters of the renal balance showed frequencies of 68% for urea >0.45g / l, 14% for creatinine >13mg / l, 50% for uric acid>68mg/l and the frequency of proteinuria of 24h having a content >0.3 is 80%. For the hepatic balance, a frequency of 18% was noted for a TGO content >40Ui/l. Finally, 18% of hypertensive pregnant women have thrombocytopenia. In this study, we showed the relative association between pregnancy complications such as hypertension and impaired metabolism in pregnant women.
Keywords: hypertension, biochemical parameters, renal balance and hepatic, impaired metabolism, pregnant women.